A Confirmation Factor Analysis of Public Compliance in Implementing Health Protocols Post Covid-19 Pandemic - Susilawati, Made; Sumarjaya, I Wayan; Octavanny, Made Ayu Dwi; Diva, Made Tresia Pramasta (International Journal of Health and Medicine, 2025)
The COVID-19 pandemic severely impacted Indonesia, leading to substantial socio-economic disruptions and widespread social anxiety. In response, the government implemented a range of measures, including restrictions and mandatory health protocols, to control the virus. Although the pandemic is officially declared over, the risk of infection remains. Therefore, continued adherence to health protocols is essential. This study aimed to identify the key factors driving public compliance with health protocols in the post-pandemic period within Indonesia, providing valuable insights for policymakers to prevent future outbreaks. The findings revealed that knowledge emerged as the most significant determinant of community adherence to ongoing health protocol implementation. Consequently, the government must consistently emphasize the importance of adhering to health protocols whenever individuals are outside their homes.